2006
DOI: 10.17221/3916-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the incidence and prevalence of lameness on Czech dairy farms

Abstract: Twenty-four Czech dairy farms were visited to record lameness prevalence and to identify factors associated with high lameness prevalence at the farm level and/or increased lameness risk at the level of individual cows. All cows were checked for lameness and forty cows per farm were examined for overgrown claws, body dirtiness and skin lesions. The farm environment was scored between 1 (excellent) to 5 (very poor) in three different aspects: floor slipperiness, cow care quality, and housing quality. Data on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Those farmers are likely to be less interested and less educated in the recognition, assessment and prevention of lameness. Poor animal care, farmers' attitudes, and herd health planning on farms were found to be important factors in cattle lameness (Mill and Ward, 1994;Bell et al, 2006;Dembele et al, 2006). Some of the DS assessed in our study were not of purulent character but had already drained.…”
Section: Importance Of Claw Healthmentioning
confidence: 63%
“…Those farmers are likely to be less interested and less educated in the recognition, assessment and prevention of lameness. Poor animal care, farmers' attitudes, and herd health planning on farms were found to be important factors in cattle lameness (Mill and Ward, 1994;Bell et al, 2006;Dembele et al, 2006). Some of the DS assessed in our study were not of purulent character but had already drained.…”
Section: Importance Of Claw Healthmentioning
confidence: 63%
“…Farms conducting routine CT only when cows were observed to have overgrown claws had higher levels of lameness [34]. In contrast, Dembele et al [35] observed no significant difference in the prevalence of lameness and overgrown claws between farms that practiced and those that did not practice continuous trimming. Likewise, the number of months that elapsed before whole herd trimming had no influence on the prevalence of overgrown claws and lameness [35].…”
Section: Claw Overgrowthmentioning
confidence: 93%
“…In addition, the management factors associated with increased lameness included not treating lame cows within 48 h of detection; insufficient time given to detecting lameness across the entire herd; and the common occurrence of severe heel erosion, interdigital growths, or toe necrosis as reported by the farmer. Other studies have shown that lameness or claw lesions were associated with comfort in the lying area (Barker et al, 2007;Fregonesi et al, 2007), quality of walking surfaces (Chesterton et al, 1989;Dembele et al, 2006), and exposure to slurry in the housing environment (Gregory et al, 2006).…”
Section: Introductionmentioning
confidence: 99%